2023
DOI: 10.3390/ijerph20043248
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Adults Aged 65 and over to Participate in Resistance Training by Linking Them with a Peer: A Pilot Study

Abstract: Resistance training (RT) is beneficial for older adults, particularly to support living independently in their home. However, fewer than 25% of older adults in Australia participate in the recommended, twice-weekly sessions. Reasons older adults do not participate in RT include not having anyone to go with or not knowing what to do. Our study linked older adults with a peer (i.e., older person already participating in RT) to help them overcome these barriers. The aim of our study was to determine whether peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In this type of training, muscles are required to exert force against an external load, and it can be safe and effective for older adults [ 26 ]. Additionally, several studies have supported the benefits of resistance training for the physical and mental health of older people [ 27 , 28 , 29 ]. Scientific research has shown that the regular practice of resistance training can significantly contribute to the prevention and management of common chronic diseases in this population, such as cardiovascular disease and type 2 diabetes [ 30 ], because it has the potential to improve sensitivity to insulin and improve glucose oxidation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this type of training, muscles are required to exert force against an external load, and it can be safe and effective for older adults [ 26 ]. Additionally, several studies have supported the benefits of resistance training for the physical and mental health of older people [ 27 , 28 , 29 ]. Scientific research has shown that the regular practice of resistance training can significantly contribute to the prevention and management of common chronic diseases in this population, such as cardiovascular disease and type 2 diabetes [ 30 ], because it has the potential to improve sensitivity to insulin and improve glucose oxidation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training is a popular form of exercise that has been extensively researched for its ability to improve the muscle strength, body composition, and overall health of individuals of all ages and genders [1,2]. However, despite studies on the numerous benefits of resistance training [3,4], there is limited research on its impact on neurotrophic factors and obesity-related markers in middle-aged women with obesity.…”
Section: Introductionmentioning
confidence: 99%